2009
DOI: 10.1021/jp808013k
|View full text |Cite
|
Sign up to set email alerts
|

UV Raman Spectroscopic Study on TiO2. II. Effect of Nanoparticle Size on the Outer/Inner Phase Transformations

Abstract: The mechanism of the size-dependent outer/inner phase transformation in ultrafine TiO 2 particles with narrowed size distribution was intensively investigated using UV Raman spectroscopy, X-ray diffraction, and transmission electron microscopy. Particle size is found to be the critical parameter determining the onset transition temperature and nucleation performance. The transformation temperature was decreased with the decrease of initial particle size. Rutile nucleates at interfaces of the contacting anatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
127
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(136 citation statements)
references
References 32 publications
(50 reference statements)
4
127
0
3
Order By: Relevance
“…It was proposed that such surface-phase junction could possibily promote charge separation across the junctions between different phases, which might be responsible for the enhanced photocatalytic activity for hydrogen evolution. 176 This synergistic effect of anatase and rutile has also been suggested in other studies. 180 Recently, Paracchino et al reported a highly active photocathode for solar H 2 production, consisting of electrodeposited cuprous oxide, which was protected against photocathodic decomposition in water by nanolayers of Al-doped zinc oxide and titanium oxide, and activated for hydrogen evolution with electrodeposited Pt nanoparticles.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…It was proposed that such surface-phase junction could possibily promote charge separation across the junctions between different phases, which might be responsible for the enhanced photocatalytic activity for hydrogen evolution. 176 This synergistic effect of anatase and rutile has also been suggested in other studies. 180 Recently, Paracchino et al reported a highly active photocathode for solar H 2 production, consisting of electrodeposited cuprous oxide, which was protected against photocathodic decomposition in water by nanolayers of Al-doped zinc oxide and titanium oxide, and activated for hydrogen evolution with electrodeposited Pt nanoparticles.…”
supporting
confidence: 74%
“…175 Although single-phase TiO 2 has been a benchmark photocatalyst with high photocatalytic activity for hydrogen production in biomass reforming, Zhang et al recently found that the photocatalytic activity could be enhanced by designing the surface phase junctions between anatase and rutile. [176][177][178][179] The size-dependent outer/inner phase transformation in TiO 2 nanoparticles with narrowed size distribution was investigated using UV Raman spectroscopy, X-ray diffraction, and transmission electron microscopy. 176 Particle size was found to be the critical parameter in determining the onset transition and nucleation temperature of TiO 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The more symmetric anatase and rutile structure gives rise to much simpler Raman spectra, with characteristic features evidenced in Figure 1b [23]. Insights into the surface/bulk distribution of phases in a TiO2 sample can be gained by a combination of common visible/IR Raman with UV Raman spectroscopy, which is more surface-sensitive due to the adsorption of UV light by TiO2 [24,25]. This approach was used to demonstrate that, in the anatase → rutile transition, rutile forms in the bulk, while anatase can persist on the surface of the sample to higher temperatures than previously thought.…”
Section: Characterizationmentioning
confidence: 99%
“…When extending the oxidation time to 10 h at 973 K, Figure 5 shows the significant change of surface microstructure, and the size of point-like structures become too large, in the case of adding 0.3% Cr. Considering the changes of surface microstructure and phase transformation, one could draw the conclusion that the phase transformation from anatase to rutile has been effected by the crystal size [31,32]. During each oxidation condition, Cr could accelerate the phase transformation from anatase to rutile, and affect the growth of crystal size, especially at suitable temperature of 973 K [25,30].…”
Section: Appearance and Phase Evolution Of Photocatalyst Composite Comentioning
confidence: 99%